TANGGUNG JAWAB PENGELOLA JALAN TOL ATAS KECELAKAAN DI JALAN TOL JAKARTA-CIKAMPEK - Khosyi Putra Ariswari; Siti Nurbaiti (Fakultas Hukum Universitas Trisakti, 2021)
The toll road is a freeway but there are many road users who feel unsafe, such as the case of car tire burst at KM 39+500 on the Jakarta-Cikampek Toll Road. The subject of the research are: what is the Responsibility of the Jakarta-Cikampek Toll Road administrators for the accident occurred at KM 39 of Cikampek Toll Road according to Law Number 38 of 2004 concerning Roads and how the Jakarta-Cikampek Toll Road administrators provides compensation to accident victims at KM 39 of Jakarta-Cikampek Toll Road. The research is normative and descriptive legal research, based on secondary data and supported by primary data. The data is analyzed qualitatively and conclusions are drawn using deductive methods. The conclusions of the research illustrate that the Jakarta-Cikampek toll road adminitrators is not responsible for the accident, in accordance with the provisions of Article 42 of Law Number 38 of 2004 concerning Roads, and the compensation provided by the Jakarta-Cikampek toll road administrators to victims is limited to material losses, not including immaterial losses. PT (Persero) Jasa Marga is considered negligent because it is proven that there are part of the roads that do not meet the minimum service standards for toll roads.